Neoadjuvant Topical Mitomycin C for an Extensive Ocular Surface Squamous Neoplasia - Vaibhav Kumar Jain; Jaya Kaushik; Savita Agarwal (Delhi Journal of Ophthalmology)
A sixty-five-year old male presented with an enlarging mass over the ocular surface involving nasal area of conjunctiva, superior and inferior fornix and covering the corneal surface obscuring pupil barring a temporal island of cornea. On the basis of clinical features and impression cytology, the diagnosis of ocular surface squamous neoplasia (OSSN) was made and patient was given neoadjuvant chemotherapy in the form of topical mitomycin C (0.04%) for 6 cycles. Excision biopsy with cryotherapy and amniotic membrane transplantation was performed. At the last follow-up, patient showed no clinical evidence of OSSN.